An objective measure for the visual fidelity of virtual reality and the risks of falls in a virtual environment. Issue 3 (September 2016) - Menzies, R.; Rogers, S.; Phillips, A.; Chiarovano, E.; Waele, C.; Verstraten, F.; MacDougall, H.
Abstract Despite decades of development of virtual reality (VR) devices and VR's recent renaissance, it has been difficult to measure these devices' effectiveness in immersing the observer. Previously, VR devices have been evaluated using subjective measures of presence, but in this paper, we suggest that postural stability can be used to objectively assess visual fidelity of VR headsets. We validated this measure by testing known differences between the devices. This study also aimed to determine the stability of healthy participants, while in a stable virtual world, compared to eyes-open and eyes-closed conditions and therefore provide a standard of safety requirements for future experimentation. Participants' ability to maintain a stable centre of pressure was measured using a Wii Balance Board, covered by a foam pad. Stability in eyes-open and eyes-closed conditions was compared with: (1) an iPod Touch in a simple Google cardboard style headset, (2) the Oculus Rift Development Kits (DK) DK1, DK2, with and without the tracking of linear head movements, and (3) the Samsung Gear VR. With a stable VR visual stimulus, the eyes-open condition allowed for significantly greater postural stability than the other conditions, which supports the validity of posturography as a measure of visual fidelity. Further, the iPod Touch, with its narrow field of view and rudimentary software, was significantly less effective at destabilising participants with visual perturbations than the other headsets, with their wider field of view and time warping. Unexpected results are discussed with respect to the possible limitations of the experimental design.